Noncytopathic Clearance of Lymphocytic Choriomeningitis Virus from the Hepatocyte - Guidotti, Luca G. (The Rockefeller University Press, 1999)
We have previously shown that interferon and tumor necrosis factor noncytopathically abolish hepatitis B virus (HBV) replication from the hepatocyte and kidney tubular epithelial cells in vivo. Here we show that a persistent lymphocytic choriomeningitis virus (LCMV) infection is cleared from the hepatocyte noncytopathically when the same cytokines are induced in the liver by antigen-nonspecific stimuli. These results indicate that, like HBV, LCMV is also susceptible to intracellular inactivation by cytokine-induced antiviral mechanisms that are operative in the hepatocyte. In contrast, LCMV is not cleared from intrahepatic nonparenchymal cells or splenocytes, indicating that, unlike the hepatocyte, these cells do not produce the factors required to inactivate LCMV. Antiviral mechanisms like these may have evolved to maintain the functional integrity of vital organs in the face of massive infection.